Bioinspired Photo-Responsive Liquid Gating Membrane - Rongrong Zhang; Jinmei Lei; Jiadai Xu; Hexuan Fu; Yuan Jing; Baiyi Chen; Xu Hou (Biomimetics, 2022)
Stomata in the plant leaves are channels for gas exchange between the plants and the atmosphere. The gas exchange rate can be regulated by adjusting the opening and closing of stoma under the external stimuli, which plays a vital role in plant survival. Under visible light irradiation, the stomata open for gas exchange with the surroundings, while under intense UV light irradiation, the stomata close to prevent the moisture loss of plants from excessive transpiration. Inspired by this stomatal self-protection behavior, we have constructed a bioinspired photo-responsive liquid gating membrane (BPRLGM) through infusing the photo-responsive gating liquid obtained by dissolving the azobenzene-based photo-responsive surfactant molecules (AzoC8F15) in N,N-Dimethylacetamide (DMAC) into nylon porous substrate, which can reversibly switch the open/closed states under different photo-stimuli. Theoretical analysis and experimental data have demonstrated that the reversible photoisomerization of azobenzene-based surfactant molecules induces a change in surface tension of the photo-responsive gating liquid, which eventually results in the reversible variation of substantial critical pressure for gas through BPRLGM under alternating UV (PCritical (off)) and visible (PCritical (on)) light irradiations. Therefore, driven by a pressure difference ΔP between PCritical (on) and PCritical (off), the reversible switches on the open/closed states of this photo-responsive liquid gating membrane can be realized under photo-stimuli. This bioinspired membrane with switchable open/closed liquid gating performance under photo-stimuli has the opportunity to be used in the precise and contactless control of microfluidics.